Resistance of Capsicum annuum genotypes against various isolates of Phytophthora capsici from Java, Indonesia - Wartono Tono; SURYO WIYONO; MUHAMAD SYUKUR; GIYANTO; PUJI LESTARI (Society for Indonesian Biodiversity, 2019)
Abstract. Wartono, Wiyono S, Syukur M, Giyanto, Lestari P. 2019. Resistance of Capsicum annuum genotypes against various isolates of Phytophthora capsici from Java, Indonesia. Biodiversitas 20: 3723-3730. Phytophthora capsici Leonian is one of the pathogenic oomycetes that can reduce chilli production worldwide. In this study, Indonesian local chilli genotypes were evaluated for their resistance to P.capsici on chilli in Java, under controlled conditions. P. capsici used in this study consisted of four isolates derived from chilli plants in Java Island. The chilli genotypes tested were 38 local chilli (Capsicum annuum L.) originated from Indonesia and 3 introduced C. annuum. Inoculation was carried out by drenching 5 ml suspension of zoospore (1 x 104) on the growing medium suitable for the oomycetes around the plant. Disease symptom was measured at 21 days after inoculation. Salicylic acid and b-1.3-glucanase analyses were conducted to 7-week old plant with specific interval. Molecular characterization to complement disease assay was carried out using SCAR primers (OpD04,717-F/D04,717-R). Significant differences were found in genotypes, isolates, and interactions between chilli genotypes x P. capsici isolates. Four tested isolates had different levels of virulence ranging from moderate (CpnsCK1, KdrRM3, WnsbCk) to high (WnsbCK2). The chilli genotypes revealed high partial resistance to P. capsici, as demonstrated by six genotypes resistant to CpnsCK1, two genotypes to KdrRM3, and one genotype resistant to WnsbCK1. Resistance of one of chilli pepper, Ungara was positively associated with an increase of salicylic acid and b-1.3-glucanase. There is no association between the SCAR marker with resistance of chilli to P. capsici suggested these pathogens from Java are probably controlled by another locus which is not detected by this SCAR marker.